The preparation and phospholipid binding property of the C2 domain of human factor VIII - Takeshima, Kazuya; Smith, Christina; Tait, Jonathan; Fujikawa, Kazuo (Thrombosis and Haemostasis, 2003)
The C2 domain of human factor VIII was expressed in a yeast secretion system and its binding properties were studied. A cDNA coding the C2 domain sequence of human factor VIII with a N-terminal six amino acids extension (C-C2) was constructed, transformed into Pichia pastoris cells and expressed. The product was purified by ammonium sulfate fractionation and anion exchange chromatography. It emerged as a single peak from both ion exchange and gel filtration columns, indicating C-C2 is a homogenous monomer. The binding activity of C-C2 to phosphatidylserine-containing phospholipid vesicles was measured by competitive binding with annexin V. The values of IC50were approximately 70nM for both factor VIII and its light chain, but were about 7000nM for C-C2. These results indicated C-C2 has 100-fold less binding affinity than factor VIII or the light chain. Direct binding to solidified phosphatidylserine-containing phospholipids also showed that C-C2 has ~50-fold less binding affinity than does the light chain. C-C2 poorly inhibited Xase activity. These results together clearly show that the C2 domain alone does not have full membrane binding activity, and suggest that the other light chain domains, A3 and/or C1, are also involved in the phospholipid binding activity of factor VIII.
Keywords: Factor VIII; C2 domain; phospholipid binding; annexin V